The Ashabul Kahfi Phenomenon Scientific Interpretation: Analysis of the Ministry of Religion's Scientific Interpretation of the Indonesia Republic: Analysis of the Ministry of Religion's Scientific Interpretation of the Indonesia Republic - Ayuna Dzil Maunah; Muhammad Faliq Mubarrok Ilmi (UIN Sulthan Thaha Saifuddin Jambi, 2025)
The story of Ashabul Kahfi contained in the Qur'an is a very clear and complete story, which aims to provide in-depth lessons and learning. This story includes themes that are in line with the main objectives of the Qur'an, known as Maqasid Al-Qur'an. The purpose of this study is to explore the understanding of knowing how the interpretation of Ashabul Kahfi is integrated with scientific explanations in the Tafsir Ilmi by the Ministry of Religion and LPMQ. This study uses a library research method with the maudhu'i method. The results of this study indicate that the interpretation of the Tafsir Ilmi Kemenag team of the story of Ashabul Kahfi shows that scientific phenomena, such as ear closing, acupuncture points that suppress appetite, cave temperature regulation, and body rotation, are in accordance with modern knowledge. This explanation illustrates that science does not conflict with the Qur'an, but can be integrated with empirical reason and reality. The Tafsir Ilmi Kemenag aims to align the Qur'an with modern knowledge, creating harmony between the two. This approach emphasizes the importance of a comprehensive understanding of revelation and science. Finally, this interpretation becomes a symbol of civilization that is able to connect religious traditions with scientific progress.